Analisis Evaluasi Pembelajaran Terpadu Di Kelas 5 SD Negeri 57 Pangkal Pinang - Iqbal Arrosyad, M; Ayu Novianti, Rahma; Rani; Indriani, Luciana (Universitas Muhammadiyah Bangka Belitung, 2023)
This study aims to determine the analysis of integrated learning evaluation in grade 5 SD Negeri 57 Pangkal Pinang. This study uses a qualitative approach. And also, this research also uses descriptive research, in which this research describes the evaluation of integrated learning in grade 5 at SDN 57 Pangkal Pinang. Based on the results of the discussion, stated that evaluation has a very important role in learning. This aims to determine the extent of students' knowledge in understanding the material that has been studied in order to make it easier for teachers to assess and measure how effective the strategies or methods that have been implemented during learning. Evaluation is also useful as a reference for teachers to improve or perfect learning activities. . Evaluation activities can be carried out by direct observation or through tests. The evaluation method in integrated learning consists of observation, self-evaluation, oral tests, question tests, and parental observations. Keywords: Evaluation, Integrated Learning